Automotive paint production line blistering improvement and approach / Wan Aazmi Wan Hamzah ... [et al.] - Wan Hamzah, Wan Aazmi; S.Z.A., Sakinah; J., Alias; N.N.M., Zawawi (Smart Manufacturing Research Institute (SMRI), 2022)
Painting the body and other elements, such as the wing or bonnet, is one of the costliest aspects of vehicle manufacturing. Surprisingly, the painting could cost even more than the body itself. The high expenses are due to the processes involved in the painting process rather than the machines used in the paint shop. From this perspective, it is evident that automobile makers constantly monitor the painting process to avoid any deviations from the desired outcome. Therefore, this paper aims to investigate the impact of blisters, one of the most common painting faults, and offered suggestions for improvement. The Ishikawa diagram was referred to measure the blister root cause. A few possible root causes were derived and then study to create a trial. The trial will show the actual result needed for the production team in order to tackle blistering issue. The setup for the painting process requires the optimal adjustment of different parameters such as humidity, temperature and the consistence of the lacquer itself. To eliminate the blister and other paint shop defect, a proper guideline and proper maintenance of the paint shop itself is really needed. While for long term solution is to have a new build up paint shop which equips with all the current technology such as the robot spray and eliminate too much rework on the unit before top coat spray. From the present analysis, it can be summarized that the major root cause of blister is the air trapped and sweat of the operator during the preparation process.